Plant-derived food bioactives in bone health: from multi-targeted roles to molecular mechanisms in osteoporosis - Zhang, Yi; Xu, Lijuan; Xu, Haofeng; Zhang, Yiran; Wang, Linxiao; Jiang, Shasha; Sun, Yan; Yu, Yan (Frontiers in Nutrition, 2026)
Osteoporosis (OP) is a metabolic bone disease characterized by reduced bone mass and deterioration of bone microstructure. Current pharmacological treatments are often associated with significant side effects and poor patient compliance. In recent years, food bioactives—such as polyphenols, carotenoids, and saponins—have attracted growing interest for their multi-target and low-toxicity profiles in the prevention and management of OP. This review systematically elaborates the protective roles and underlying molecular mechanisms of these compounds against OP. Polyphenols exert beneficial effects through antioxidant, anti-inflammatory, and bone metabolism-regulating properties, as well as via modulation of the gut–bone axis. Their mechanisms involve key signaling pathways, including PI3K/Akt, sirtuin 1 (SIRT1)/forkhead box O3a (FOXO3a), Hippo/YAP, reactive oxygen species (ROS)/HIF-1α, and Wnt/β-catenin. Carotenoids, which are potent antioxidants, contribute to a reduced risk of OP by alleviating oxidative stress and cellular senescence, including the senescence-associated secretory phenotype (SASP). Saponins regulate bone remodeling bidirectionally through pathways such as PI3K/Akt/mTOR, bone morphogenetic protein 2 (BMP-2)/runt-related transcription factor 2 (Runx2), and RANKL/osteoprotegerin (OPG). They also inhibit NF-κB/mitogen-activated protein kinase (MAPK) signaling and downregulate osteoclast-related transcription factors, including c-Fos and NFATc1. Given their efficacy and safety, food bioactives represent a valuable source of novel nutraceuticals for bone health.